Monitoring the quality of public consultations with trade unions on implementation of the National Recovery and Resilience Plans - Sebastiano Sabato; Angelina Atanasova; Ludovico Fiorucci; Slavina Spasova (European Trade Union Institute (ETUI), 2023)
In response to the Covid-19 pandemic, the European Council agreed to provide major financial support to Member States. Drawing on a combination of the EU's long-term budget (2021-2027) and an additional temporary support system known as 'NextGenerationEU' (NGEU), the EU has been providing funds to help Member States with the fall-out from the Covid-19 crisis. The so-called 'Recovery and Resilience Facility' (RRF), at the core of the NGEU, provides financial support to Member States, notably through a combination of grants and loans (European Parliament and Council of the EU 2021). Resources made available through the RRF amount to 672.5 billion euros (360 billion euros in loans and 312.5 billion euros in grants - in 2018 prices). To access the RRF funds, Member States submitted detailed national Recovery and Resilience Plans (RRPs), in which they set out reforms and investments to be completed by 2026. In particular, RRPs are supposed to identify measures in policy areas of European relevance, structured in six pillars, deemed as key to achieving recovery from the Covid-19 crisis and to enhancing the long-term resilience of the EU and of its Member States (European Parliament and Council of the EU 2021: recital 10): (i) green transition; (ii) digital transformation; (iii) smart, sustainable and inclusive growth; (iv) social and territorial cohesion; (v) health, and economic, social and institutional resilience; and (vi) policies for the next generation, children and young people. In order to assess the adequacy of the RRPs, a set of criteria have been established, including their contribution to the green and digital transitions and to the implementation of the European Pillar of Social Rights (EPSR), as well as their consistency with the European Semester Country-specific Recommendations (CSRs) which the Member States received in previous years (European Parliament and Council of the EU 2021: recital 42). Reforms and investments linked to the RRF's 'social and territorial cohesion' pillar are expected to help strengthen social dialogue in the Member States (European Parliament and Council of the EU 2021: recital 14); more generally, in drafting their RRPs, the Member States have been asked to report on how they conducted consultations with relevant national stakeholders, including the social partners and civil society organisations.
Keywords: 330; Stabilisierungspolitik; Wirtschaftskrise; Coronavirus; Gewerkschaft; EU-Staaten